A Customizable IoT Platform Developed Using Low-Code - Lopes, João Pedro Delgado (2021)
In nowadays’ societies and businesses’ ecosystems of acceleration, it is of most importance the digitalization of the formers. In this sense, Internet of Things (IoT) emerges to connect devices to the internet, allowing the access to large amounts of data and, through its analysis, to act upon it. An IoT platform allows, among others, to manage IoT devices. Nonetheless, its development is still a complex and expensive process that requires high technical knowledge. To accelerate developments when building IoT applications, this thesis proposes the use of Low-Code platforms, such as Outsystems. To improve the user experience, an embedded customizable dashboard is included in the platform. To achieve this, a reusable Forge component was built and is currently available for download and in use by the community. This component allows to provide drag and drop functionalities to both web and mobile applications. In this case, it will allow the reordering of dashboard cards to personalize dashboards. Another component that enables barcode/qr code reading by Zebra devices is also included in this thesis. To assess the developed IoT platform, an IoT device prototype was created, using an Arduino with an ESP module, as well as a set of sensors and actuators that communicate with the IoT platform via the Message Queuing Telemetry Transport (MQTT) protocol.